The perception on technology acceptance to the behaviors on the use of social media for marketing and its implications on the turnover of creative industry MSMEs in villages. (March 2019) - Febrianty,; Divianto,; Hidayat, Rahmat; Fatmariani,; Rohana, Tulus
Abstract: MSMEs require an effective and efficient marketing medium to expand their market shares. Thus, the role of social media for marketing is greatly important. The purpose of this study is to examine the technological acceptance factors to the behaviors on the use of social media for marketing and its implication on the turnover of creative industry SMSEs. This research employs the Technology Acceptance Model (TAM) and Theory of Planned Behavior (TPB). The research population consists of creative industry MSMEs in Banyuasin Regency, based on the convenience sampling method. There are 78 respondents of business actors in Banyuasin Regency. The data are collected through questionnaires and then analyzed using the Structural Equation Modeling (SEM) operated with Lisrel Program. The research results show that: The indirect influence of variable Perceived Usefulness (X1) on Intention to Continue Usage of Social Media Marketing (Y1) and MSMEs' turnover (Y2) is equal to 0.05. The indirect influence of variable Perceived Enjoyment (X2) on Intention to Continue Usage of Social Media Marketing (Y1) and its implication on MSMEs' turnover (Y2) is equal to 0.08. The indirect influence magnitude of variable Intellectual Capital (X3) on Intention to Continue Usage of Social Media Marketing (Y1) and its implication on MSMEs' turnover (Y2) is equal to 0.11. The indirect influence magnitude of variable Risk or Perceived Costs (X4) on Intention to Continue Usage of Social Media Marketing (Y1) and MSMEs' turnover (Y2) is equal to 0.11.